Organizational Characteristics and Financial Performance of Multi-purpose Cooperatives: Evidence from North Eastern Mindanao, Philippines - Miranda, Kimberly L. (International Review of Management and Marketing, 2026)
This study examined the financial performance of multi-purpose cooperatives and determined whether selected organizational characteristics predict financial performance. Using a quantitative, descriptive-predictive design, documentary data from cooperative records and audited financial statements were analyzed. Financial performance was assessed using the PISO framework in terms of profitability, institutional strength, structure of assets, and operational strength. The organizational characteristics examined were capital build-up, number of members, number of employees and staff, and years in operation. Descriptive statistics, quadratic regression, and one-way ANOVA were used for analysis. Results showed that small size cooperative achieved satisfactory financial performance, while the others were classified under needs improvement. Operational strength was the strongest dimension, whereas institutional strength was the weakest. Capital build-up and number of members significantly predicted financial performance, while number of employees and staff and years in operation did not. Significant differences in performance were also observed across cooperative types. The findings highlight the importance of capital formation and membership participation in improving cooperative financial sustainability.